X-Ray Photoemission Study of the Oxidation of Hafnium. (25th November 2008) - Chourasia, A. R.; Hickman, J. L.; Miller, R. L.; Nixon, G. A.; Seabolt, M. A.
Abstract : About 20 Å of hafnium were deposited on silicon substrates using the electron beam evaporation technique. Two types of samples were investigated. In one type, the substrate was kept at the ambient temperature. After the deposition, the substrate temperature was increased to 100, 200, and300 ∘ C . In the other type, the substrate temperature was held fixed at some value during the deposition. For this type, the substrate temperatures used were 100, 200, 300, 400, 500, 550, and600 ∘ C . The samples were characterized in situ by the technique of X-ray photoelectron spectroscopy. No trace of elemental hafnium is observed in the deposited overlayer. Also, there is no evidence of any chemical reactivity between the overlayer and the silicon substrate over the temperature range used. The hafnium overlayer shows a mixture of the dioxide and the suboxide. The ratio of the suboxide to dioxide is observed to be more in the first type of samples. The spectral data indicate that hafnium has a strong affinity for oxygen. The overlayer gets completely oxidized to formHfO 2 at substrate temperature around300 ∘ C for the first type of samples and at substrate temperature greater than550 ∘ C for the second type.